(untitled) (American Journal of Islam and Society, 2015)
Mahmoud Cherif Bassiouni is a distinguished human rights advocate with an astounding career and publication record that exceeds seventy books (authored and edited) and 260 articles. The Sharī‘a and Islamic Criminal Justice is yet another rigorous contribution that should enrich and broaden the scope of the criminal law debate in the Islamic legal system and its relevance to international humanitarian law. The significance of this work lies especially in the Book Reviews 107 author’s sincere endeavor to derive appropriate tools from Islamic law to address contemporary issues of post-conflict and transitional justice. The first chapter, an introductory review of key conceptual constructs and historical developments, examines various topics from the evolution of Islamic legal theory and the Sunni and Shi‘i schools of law to the resurgence of Islamic thought during the nineteenth and twentieth centuries. In regard to Islamic law’s historical pertinence to issues related to war and peace, the author elaborates especially on two categories: dār al-ḥarb (the house of war) and dār al-silm (the house of peace). Finally, he illustrates four types of treaties: those of peace (salām), truce (hudnah), protection (dhimmah), and safe conduct (amān) ...